2008
DOI: 10.1016/j.neuroscience.2008.03.049
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular and subsynaptic localization of group I metabotropic glutamate receptors in the nucleus accumbens of cocaine-treated rats

Abstract: There is significant pharmacological and behavioral evidence that group I metabotropic glutamate receptors (mGluR1a and mGluR5) in the nucleus accumbens play an important role in the neurochemical and pathophysiological mechanisms that underlie addiction to psychostimulants. To further address this issue, we undertook a detailed ultrastructural analysis to characterize changes in the subcellular and subsynaptic localization of mGluR1a and mGluR5 in the core and shell of nucleus accumbens following acute or chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 55 publications
(108 reference statements)
1
24
0
Order By: Relevance
“…Mice were transcardially perfused with Ringer's solution followed by a fixative containing 4% paraformaldehyde and 0.1% glutaraldehyde in phosphate buffer (0.1 M; pH 7.4). Tissue was cut, labeled using preembedding immunoperoxidase staining with RGS14 monoclonal antibody, and prepared for EM as described (45). Sections were examined on the Zeiss EM-10C electron microscope.…”
Section: Methodsmentioning
confidence: 99%
“…Mice were transcardially perfused with Ringer's solution followed by a fixative containing 4% paraformaldehyde and 0.1% glutaraldehyde in phosphate buffer (0.1 M; pH 7.4). Tissue was cut, labeled using preembedding immunoperoxidase staining with RGS14 monoclonal antibody, and prepared for EM as described (45). Sections were examined on the Zeiss EM-10C electron microscope.…”
Section: Methodsmentioning
confidence: 99%
“…A single injection of cocaine decreases the proportion of plasma membrane-bound mGluR1a in the NAc shell dendrites 45 minutes after the injection, while chronic cocaine treatment decreased mGluR1a in the NAc core dendrites. This is in contrast to acute and chronic cocaine treatment having no effect on the localization of mGluR5 receptors (Mitrano et al, 2008). Another study found a decrease in mGluR1a in the NAc shell of chronic cocaine treated rats (Ary and Szumlinski., 2007;Uys and LaLumiere., 2008).…”
Section: Metabotropic Receptors and Cocainementioning
confidence: 90%
“…Acute and chronic cocaine treatment alter the normal function, expression or traficking of group I metabotropic receptors in the NAc of rats (Mitrano et al, 2008). A single injection of cocaine decreases the proportion of plasma membrane-bound mGluR1a in the NAc shell dendrites 45 minutes after the injection, while chronic cocaine treatment decreased mGluR1a in the NAc core dendrites.…”
Section: Metabotropic Receptors and Cocainementioning
confidence: 99%
“…The intracellular localization of mGlu5 receptors has been well documented. Electron microscopy studies revealed that the mGlu5 receptor not only localizes on postsynaptic membranes and extrasynaptic regions but that most of this receptor is intracellular (Hubert et al, 2001;López-Bendito et al, 2002;O'Malley et al, 2003;Kuwajima et al, 2004;Mitrano et al, 2008Mitrano et al, , 2010. For example, 50-90% of mGlu5 receptors localize to different intracellular membranes in many different brain regions (Hubert et al, 2001;Paquet and Smith, 2003;Kuwajima et al, 2004).…”
Section: Intracellular Mglu5 Receptorsmentioning
confidence: 99%
“…Ultrastructure studies also revealed large numbers of mGlu5 receptor gold particles on ER membranes (O'Malley et al, 2003;Mitrano and Smith, 2007;Mitrano et al, 2008Mitrano et al, , 2010. To show functionality of ER-localized mGlu5 receptors, we 1) uncaged 4-methoxy-7-nitroindolinyl-glutamate using laser-induced photolysis onto dendrites in the presence of mGlu5 receptor impermeable antagonists as well as other ionotropic and metabotropic receptor antagonists (Purgert et al, 2014), and 2) we puffed quisqualate onto a dendrite in the presence of the same inhibitors (Y.J.…”
Section: Intracellular Mglu5 Receptorsmentioning
confidence: 99%